International criminal tribunals and the perception of justice: the effect of the ICTY in Croatia - David, Roman (International journal of transitional justice, 2014)
This article examines the impact of international criminal tribunals (ICTs) on the perception of justice. From the legal perspective, the perception of ICTs as just partly stems from their impartiality in dealing with perpetrators of different nationalities/ethnicities. In contrast, social identity theory suggests that the perception of ICTs as just is determined by the group membership, as people tend to pass more lenient judgments on perpetrators from their in-group. In order to resolve this dilemma, we developed an experimental vignette that manipulated international versus national courts, in-group versus out-group perpetrators and a jail sentence versus no jail sentence. The vignette was embedded in a representative survey conducted in Croatia in 2008 and combines with a natural experiment on the Radovan Karadžić arrest. The findings reveal biased perceptions of justice, conditional support for the ICTY, the dual impact of deterrent effect and the positive effect of the apprehension of war criminals.